Bulgaria : Financial Sector Assessment Program: Technical Note-Stocktaking of Progress Achieved by the Bulgarian National Bank in Strengthening Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note evaluates the progress achieved by the Bulgarian National Bank (BNB) in strengthening banking supervision in Bulgaria. Progress in responding to the recommendation of the 2015 Basel Core Principles Assessment is under way. As part of the reforms initiated in October 2015, the BNB has put in place a new governance model to enhance the effectiveness of supervision. The activities of the Banking Supervision Department (BSD) will now be governed by new formal policies adopted by the Governing Council (GC). Through a new quarterly report, the GC is now better informed on banking risks and progress in addressing them. The BSD is also subject to annual internal audit.